2020
DOI: 10.34117/bjdv6n5-242
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic immobilization of Burkholderia cepacia lipase onto octyl-silica for synthesis of flavors esters

Abstract: Burkholderia cepacia lipase (BCL) was immobilized onto silica modified with octyl groups (OS) and the biocatalyst (BCL-OS) was evaluated as its performance in the synthesis in organic medium (synthesis of flavor esters as a model). The maximum support loading was 0.375 genzyme/gsupport, yielding a biocatalyst with an activity of 1197 U/gsupport at pH 7.0 and 50 °C in the hydrolysis of olive oil. The biocatalyst BCL-OS showed to be 9-fold more stable than the free lipase at 60°C in buffer solution (absence of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…Some strategies can be used to improve yields and productivity in the presence of inhibitors, like the use of higher biocatalyst concentrations to increase process rate or the detoxification of the hydrolysate before fermentation. Arruda et al (2008) studied the detoxification of sugarcane bagasse hemicellulose acid hydrolysate and observed that the use of adsorption on activated carbon was effective in reducing the inhibitory compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Some strategies can be used to improve yields and productivity in the presence of inhibitors, like the use of higher biocatalyst concentrations to increase process rate or the detoxification of the hydrolysate before fermentation. Arruda et al (2008) studied the detoxification of sugarcane bagasse hemicellulose acid hydrolysate and observed that the use of adsorption on activated carbon was effective in reducing the inhibitory compounds.…”
Section: Resultsmentioning
confidence: 99%
“…The model reagent chosen to represent the carboxylic acids present in vegetable oils was oleic acid. The alcohol used was ethanol (EtOH) (BARBOSA et al, 2020;CANNILLA et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some lipases need a certain amount of water to maintain their own conformation (LI et al, 2012). Another important aspect is that, like Burkholderia cepacia lipase (BCL), some have the catalytic site protected by a protein structure, the lid or lid, which may be closed rendering the enzyme inactive, but in the presence of the oil-water interface, the lid opens and leaves exposed the active site so that catalysis occurs (BARBOSA et al, 2020;NIGAM et al, 2014).…”
mentioning
confidence: 99%